2008
DOI: 10.1097/ico.0b013e31816a628d
|View full text |Cite
|
Sign up to set email alerts
|

Creutzfeldt-Jakob Disease in Recipients of Corneal Transplants

Abstract: It is likely that these 4 recipients of transplanted corneas had sporadic CJD. Because of the many corneal transplantations performed each year in the United States, occasional cases of sporadic CJD in this population are expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…In our study, none of the 3 reported systemic infections were definitively confirmed to be because of the donor tissue. Maddox et al 23 reported the incidence of sporadic CJD cases unrelated to donor tissue, based on a review of 4 cases over a 16-year period, to occur in 1 case every 1.5 years.…”
Section: Fungal Infectionsmentioning
confidence: 98%
“…In our study, none of the 3 reported systemic infections were definitively confirmed to be because of the donor tissue. Maddox et al 23 reported the incidence of sporadic CJD cases unrelated to donor tissue, based on a review of 4 cases over a 16-year period, to occur in 1 case every 1.5 years.…”
Section: Fungal Infectionsmentioning
confidence: 98%
“…Mesmo tecidos avasculares como a córnea, já demonstraram ser meios de contaminação e transmissão (1) . Há relatos de infecções causadas por bactérias, fungos, vírus e mesmo príons adquiridos por transplante de córnea (1)(2)(3)(4)(5)(6) . A legislação brasileira não permite o uso de tecidos para transplante, cujo doador apresente sorologia positiva para hepatite B, hepatite C ou HIV (7) .…”
Section: Resumo Introduçãounclassified
“…She had received a corneal graft 18 months before her illness developed from a donor with autopsy-confirmed CJD. A number of other cases of CJD in cornea recipients are likely to be coincidental cases unrelated to the corneal allograft (Maddox et al 2008;Armitage et al 2009). There has been a report of a possible association between CJD and tympanic membrane closure with allograft pericardium (Tange et al 1990), but there were no donor details to suggest that the donor had the disease and the association with this tissue transplant cannot be considered proven.…”
Section: Introductionmentioning
confidence: 97%